2013
DOI: 10.1002/ijc.28311
|View full text |Cite
|
Sign up to set email alerts
|

Serum interferon gamma level predicts recurrence in hepatocellular carcinoma patients after curative treatments

Abstract: Host immunity may have important role in the prognosis of hepatocellular carcinoma (HCC). The aim of this study was to evaluate the correlation between circulating immune regulators and clinical outcome in patients with HCC. Sixty-three HCC patients were prospectively enrolled. Serum levels of interleukin-10 (IL-10), transforming growth factor-beta (TGF-b), interferon-gamma (IFN-c) and interferon gamma-inducible protein 10 (IP-10) were measured, as well as the prevalence of regulatory T cells (Treg), Hepatocel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 43 publications
4
34
0
2
Order By: Relevance
“…In present study, we found that HCC patients with high leukocyte mtDNA content had an increased percentage of Tregs and the decreased percentage of NK-cells in peripheral blood, suggesting that mtDNA content may be involved in the immunosuppression of HCC patients. Moreover, it has been reported that IFN-γ and TNF-α levels in plasma are associated good prognosis of HCC [31, 32], while TGF-β1 plasma concentration is associated with poor prognosis of HCC [33]. IFN-γ is one of the key mediator of cytotoxicity secreted by NK cells, while TNF-α enhances the functions of NK cells and suppress the functions of Tregs.…”
Section: Discussionmentioning
confidence: 99%
“…In present study, we found that HCC patients with high leukocyte mtDNA content had an increased percentage of Tregs and the decreased percentage of NK-cells in peripheral blood, suggesting that mtDNA content may be involved in the immunosuppression of HCC patients. Moreover, it has been reported that IFN-γ and TNF-α levels in plasma are associated good prognosis of HCC [31, 32], while TGF-β1 plasma concentration is associated with poor prognosis of HCC [33]. IFN-γ is one of the key mediator of cytotoxicity secreted by NK cells, while TNF-α enhances the functions of NK cells and suppress the functions of Tregs.…”
Section: Discussionmentioning
confidence: 99%
“…32,38,60,61 Two studies found a correlation with poor survival, 41,62 while three studies did not find a significant correlation. 33,63,64 Two studies focused on a different aspect of the Th17 response and are included in the overview in Table 1 for completeness, but not in the quantitative analyses. 65,66 Notably, while two studies reported on a correlation between a high number of Th17 cells and poor prognosis, twice as many studies (n D 4) reported on a correlation with improved prognosis (see Table 2).…”
Section: A High Number Of Th17 Cells In Peripheral Blood Is Correlatementioning
confidence: 99%
“…Serum interferon-γ levels may reflect host’s anti-tumor immunity and may be potential marker of HCC recurrence after curative therapy in patients [47]. …”
Section: Immune Suppression In Hccmentioning
confidence: 99%